The generic structure of postgraduate students' gratitute expression in the thesis acknowledgements : a linguistic analysis - Noor Suhailie binti Che Ghani (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
In academic writing, the acknowledgment section is considered as a rhetorical section that is obligatory. Thus, it could be considered as a part of academic writing even though it seems a personal piece of writing. Compared to other sections like the abstract, introduction, discussion, findings and conclusion, the acknowledgement section seems to receive very little attention from genre analysts. However, an awareness of the rhetorical structures of different genre is useful and necessary because this will help English teachers to know how language is used in various contexts. The objectives of this study are to investigate if postgraduate students use different move structures as well as examine the linguistic elements employed in postgraduate students' thesis acknowledgements. Additionally, it also aims to investigate if postgraduate students of different faiths use different generic structures in the writing of thesis acknowledgement. This study analysed 100 acknowledgement sample texts of 50 Muslim and 50 non-Muslim postgraduate students from two public universities in Malaysia. This study used the move structures in English thesis acknowledgements frameworks of Hyland (2004) and Al-Ali (2006) as well as adopted Hyland and Tse's (2004) framework of linguistic elements in expressing gratitude in order to answer all research questions. Based on the findings, Muslim and non-Muslim postgraduate students acknowledgement texts were found to consist of reflecting move, thanking move and announcing move. It was also discovered that there are three important linguistic elements in acknowledgment texts, which are patterns of expressing gratitude, modifying thanks and choice of authorial subjects. Additionally, in the Malaysian context, it was found that differences in faith do not really influence postgraduate students in writing thesis acknowledgement with the exception of divine appreciation step. The analysis of this study would benefit English teachers in order to teach appropriate ways of writing and using lexical choices in acknowledgements and also benefits the postgraduate students in composing thesis acknowledgements that meet the expectations of the academic community